Horizontal and Vertical Transfer of Oral Microbial Dysbiosis and Periodontal Disease. (December 2019) - Payne, M.A.; Hashim, A.; Alsam, A.; Joseph, S.; Aduse-Opoku, J.; Wade, W.G.; Curtis, M.A.
One of the hallmark features of destructive periodontal disease, well documented over the last 50 y, is a change to the quantitative and qualitative composition of the associated microbiology. These alterations are now generally viewed as transformational shifts of the microbial populations associated with health leading to the emergence of bacterial species, which are only present in low abundance in health and a proportionate decrease in the abundance of others. The role of this dysbiosis of the health associated microbiota in the development of disease remains controversial: is this altered microbiology the driving agent of disease or merely a consequence of the altered environmental conditions that invariably accompany destructive disease? In this work, we aimed to address this controversy through controlled transmission experiments in the mouse in which a dysbiotic oral microbiome was transferred either horizontally or vertically into healthy recipient mice. The results of these murine studies demonstrate conclusively that natural transfer of the dysbiotic oral microbiome from a periodontally diseased individual into a healthy individual will lead to establishment of the dysbiotic community in the recipient and concomitant transmission of the disease phenotype. The inherent resilience of the dysbiotic microbial community structure in diseased animals was further demonstrated by analysis of the effects of antibiotic therapy on periodontally diseased mice. Although antibiotic treatment led to a reversal of dysbiosis of the oral microbiome, in terms of both microbial load and community structure, dysbiosis of the microbiome was reestablished following cessation of therapy. Collectively, these data suggest that an oral dysbiotic microbial community structure is stable to transfer and can act in a similar manner to a conventional transmissible infectious disease agent with concomitant effects on pathology. These findings have implications to our understanding of the role of microbial dysbiosis in the development and progression of human periodontal disease.